POTENSI PENYELEWENGAN ALOKASI DANA DESA DI KAJI MENURUT PERATURAN MENTERI DALAM NEGERI NOMOR 37 TAHUN 2007 TENTANG PENGELOLAAN KEUANGAN DESA - Yuyun Yulianah (Jurnal Hukum Mimbar Justitia, 2015)
A lot of government aid which is allocated for village development is kind ofgovernment attention to rural areas. However, in this case the potency of Villagefinancial fraud is more likely to happen. It is not apart from the lack of thesupervision from district government officials on the funds flow process. In addition,which is also important is the human resources of government officials in the villageitself were generally weak. The amount of the Village Fund Allocation (ADD)received by the Head of Village is quite small and is not comparable with theresponsibility of the head of the village which is expected to organize villagedevelopment. Even worse, the ADD fraud culture by unscrupulous bureaucracy hascaused the fund received by the village was pretty small.Keywords: Regional Autonomy, Village Fund Allocation.